Storytelling in the development communication studies locating the narrative of participation through the interpretive lens - Custodio, Pamela A. (The Philippine Journal of Development Communication, 2008)
Researches in development communication are dominated by methodologies situated in the discourse of representation (Mumby, 1997), of the modernist worldview, of determining and measuring effectiveness, of mapping information flows, and of establishing casual and network relationships (Ables, 2003). Studies concerning the notion of participation have been about finding the behavioral variables that contribute to participation in terms of the "seen", i.e., engagement in activities and sharing among stakeholders (Rajan, 1993; Custodio, 1998; Gonzalves, et. al., 2005).